Design proposal of air conditioning system for block A UiTM Arau / Mohd Izham Mohd Idris and Muhd Ridzo Fadzly Rosely - Mohd Idris, Mohd Izham; Rosely, Muhd Ridzo Fadzly (2003)
Air conditioning is one of many ways to cold the hot air. Either natural or mechanical. But in this project we specific to the mechanical ways and the cooling tower chiller system is a system that we use. We want to show what is the cooling tower really are and what is the purpose that we choose this type of air conditioning system. In this book, we also show our propose project at the block A at University Technology MARA, Arau Campus.